2021
DOI: 10.34044/j.anres.2021.55.1.02
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of monoterpene compounds for control of rice pest Pomacea canaliculata

Abstract: Pomacea canaliculata (golden apple snail) is one of the most destructive and invasive rice pests in Southeast Asia and Thailand. This work focused on the molluscicidal efficiency of thymol, eucalyptol, and linalool against P. canaliculata under laboratory conditions. All essential oils made the snail motionless, closed its operculum shell, turned the soft body at the spire reddish and typically caused death within 24 hr. The toxicity levels of P. canaliculata after being exposed to the three essential oil comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
(61 reference statements)
1
1
0
Order By: Relevance
“…Herein, the monoterpenes in the EOs were potent insecticides. As previously established, the bioactivities of the EOs against insects might be correlated with their contents of monoterpenes with proven insecticidal bioactivities, such as eugenol, carvacrol, thymol, p-cymene, γ-terpinene, 1,8 cineol, terpinene-4-ol and carvone [6,10,26,47,48]. Among the monoterpenes in the thyme EO studied in the present study, carvacrol and thymol showed pronounced bioactivities against T. granarium.…”
Section: Ache Inhibitionsupporting
confidence: 74%
See 1 more Smart Citation
“…Herein, the monoterpenes in the EOs were potent insecticides. As previously established, the bioactivities of the EOs against insects might be correlated with their contents of monoterpenes with proven insecticidal bioactivities, such as eugenol, carvacrol, thymol, p-cymene, γ-terpinene, 1,8 cineol, terpinene-4-ol and carvone [6,10,26,47,48]. Among the monoterpenes in the thyme EO studied in the present study, carvacrol and thymol showed pronounced bioactivities against T. granarium.…”
Section: Ache Inhibitionsupporting
confidence: 74%
“…Among the monoterpenes in the thyme EO studied in the present study, carvacrol and thymol showed pronounced bioactivities against T. granarium. These monoterpenes have received special attention in EO research, and they have been widely evaluated as pesticides against many pests, including those that infest stored grains [13,16,[47][48][49][50][51][52][53]. The insecticidal properties of carvacrol and thymol correlated with their abilities to cause disorganization in bio-membranes, leading to the loss of permeability [49].…”
Section: Ache Inhibitionmentioning
confidence: 99%